Procedural outcomes in patients with dual versus single antiplatelet therapy prior to transcatheter aortic valve replacement - Seoudy, Hatim; Thomann, Maren; Frank, Johanne; Lutz, Matthias; Pühler, Thomas; Lutter, Georg; Müller, Oliver J.; Frey, Norbert; Saad, Mohammed; Frank, Derk (Scientific reports, 2021)
The impact of uninterrupted dual antiplatelet therapy (DAPT) on bleeding events among patients undergoing transcatheter aortic valve replacement (TAVR) has not been well studied. We conducted an analysis of 529 patients who underwent transfemoral TAVR in our centre and were receiving either DAPT or single antiplatelet therapy (SAPT) prior to the procedure. Accordingly, patients were grouped into a DAPT or SAPT group. Following current guidelines, patients in the SAPT group were switched to DAPT for 90 days after the procedure. The primary endpoint of our analysis was the incidence of bleeding events at 30 days according to the VARC-2 classification system. Any VARC-2 bleeding complications were found in 153 patients (28.9%), while major/life-threatening or disabling bleeding events occurred in 60 patients (11.3%). Our study revealed no significant difference between the DAPT vs. SAPT group regarding periprocedural bleeding complications. Based on multivariable analyses, major bleeding (HR 4.59, 95% CI 1.64-12.83, p = 0.004) and life-threatening/disabling bleeding (HR 8.66, 95% CI 3.31-22.65, p < 0.001) events were significantly associated with mortality at 90 days after TAVR. Both pre-existing DAPT and SAPT showed a comparable safety profile regarding periprocedural bleeding complications and mortality at 90 days. Thus, DAPT can be safely continued in patients undergoing transfemoral TAVR.